2012
DOI: 10.1016/j.clinbiomech.2011.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic impression insole in rheumatoid foot with metatarsal pain

Abstract: Dynamic impression insoles effectively relieve metatarsal pain because of a larger weight-bearing area. Forefoot shape during walking should be taken into consideration in orthotic designs for maximum pressure reduction. Consequently, we recommend using materials with memory properties to dynamically accommodate painful metatarsal heads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 21 publications
3
23
0
1
Order By: Relevance
“…Non-pharmacological interventions for RA that include foot orthoses and footwear can reduce pain and disability and improve long-term outcomes with existing and potential foot problems [8]. Previous studies have reported on the clinical effectiveness of foot orthoses in people with established RA, ranging from simple insoles to customised foot orthoses [9][10][11][12]. Clark [13] reported that few studies have undertaken a cost effectiveness analysis to investigate the cost implication of the prescription of foot orthoses for people with established RA, despite the high prevalence of foot involvement and the high direct cost of RA related health care to the UK economy.…”
Section: Introductionmentioning
confidence: 99%
“…Non-pharmacological interventions for RA that include foot orthoses and footwear can reduce pain and disability and improve long-term outcomes with existing and potential foot problems [8]. Previous studies have reported on the clinical effectiveness of foot orthoses in people with established RA, ranging from simple insoles to customised foot orthoses [9][10][11][12]. Clark [13] reported that few studies have undertaken a cost effectiveness analysis to investigate the cost implication of the prescription of foot orthoses for people with established RA, despite the high prevalence of foot involvement and the high direct cost of RA related health care to the UK economy.…”
Section: Introductionmentioning
confidence: 99%
“…The main function of the orthotic insoles used in this study was to reduce the peak pressure under the heel [12], because the elastic insole material deforms at each walking step, increasing the contact area with the foot [25]. These Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the calcaneus and tibia, gravity center of foot would be affected after orthosis (Stacoff et al 2000;Hayakawa 2012). The mean pain index of the metatarsal head was significantly reduced from 7.6 to 1.1 using dynamic impression insole (Chang et al 2012 Figure 1(a)). The insole with a thickness of 6 mm was developed by CATIA V5 (CATIA Dassault System Corporation, France) ( Figure 1(b)).…”
Section: Introductionmentioning
confidence: 99%